Anti-Oral Microbial Effect of Ethanol Extract of Angelica gigas Nakai - Soon-Jeong Jeong (The Korean Society of Dental Hygiene Science, 2024)
Background: The Korean name for Angelica gigas Nakai (AGN) is Cham-dang-gui, which grows naturally or is cultivated, and its dried roots are used in traditional herbal medicines. The AGN root exert various pharmacological effects. Despite the various pharmacological effects of the AGN root, there are no reports on its anti-oral microbial effects. The purpose of this study was to reveal the anti-oral microbial effect and the microbial and biochemical changes in oral microorganisms according to the concentration of the ethanol extract of AGN (EAGN) root, and to confirm the possibility of using EAGN as a plant-derived functional substance for controlling oral infectious microorganisms.Methods: Disk diffusion test, growth measurement, biofilm formation assay, and measurements of acid production and buffering capacity were performed to confirm the antibacterial effect of EAGN. Results: EAGN showed anti-oral bacterial effects against Streptococcus mutans and Aggregatibacter actinomycetemcomitans at all concentrations, with S. mutans showing a more susceptible effect at concentrations above 5.0 mg/ml and A. actinomycetemcomitans at 3.75 mg/ml. EAGN treatment significantly reduced A. actinomycetemcomitans growth at all concentrations tested. Biofilm formation was significantly reduced at concentrations above 3.75 mg/ml for S. mutans and 2.5 mg/ml for A. actinomycetemcomitans. Acid production in S. mutans and A. actinomycetemcomitans was significantly increased by treatment with EAGN, and the buffering capacities of S. mutans and A. actinomycetemcomitans increased from an EAGN concentration of 3.75 mg/ml and above. Conclusion: EAGN showed anti-oral bacterial effects against both S. mutans and A. actinomycetemcomitans at concentrations above 3.75 mg/ml, which were thought to be related to the inhibition of their growth and biofilm formation. Therefore, EAGN can be used as a safe functional substance derived from medicinal plants owing to its antibacterial effects against S. mutans and A. actinomycetemcomitans.